KEANEKARAGAMAN JENIS DAN KEPADATAN GASTROPODA DI BERBAGAI SUBSTRAT BERKARANG DI PERAIRAN PANTAI TIHUNITU KECAMATAN PULAU HARUKU KABUPATEN MALUKU TENGAH - Marlen Persulessy; Ine Arini (Program Studi Pendidikan Biologi FKIP Unpatti, 2018)
Background: Indonesia has a very high diversity of flora and fauna, including various marine biota. The diversity of marine biota varies greatly and can represent all phyla in the Pacific region of Indonesia. The purpose of this study was to determine the environmental factors, the value of diversity and the density of gastropods in the coastal waters of Tihunitu. Methods: This study was conducted on July 19, 2018. The type of research used is a descriptive type of research to see the value of diversity and density. Results: The measurement of environmental factors shows that the temperature values ​​on transect I range from 26.5-28, ° C. The second transect ranged from 27.1-29.7, ° C. The transect III ranges from 28.0-29.8, ° C. The PH value on transect I ranges from 7.4-74. The transect II ranges from 7.2-7.4. The transect III ranges from 7-7.3. The salinity value on transect I ranged from 24-34 (‰). The transect II ranges from 26-39 (‰). The transect III ranges from 25-29 (‰). The value of dissolved oxygen on transect I ranged from 7.3 to 8.3 mg / 1. On transect II ranged from 6.9-723 mg / 1. The transect III ranges from 7.1-7.2 mg / 1. While the results of determining the type of substrate visually descriptive showed that Tihun Beach has 2 types of substrate types, namely sandy and rocky. Conclusion: Gastropods found in Tihun coastal waters are 37 species representing 14 families in the phylum of molluscs. With the average value of diversity in the research station is classified as moderate, namely 3,448.6. The highest density value is 0.108 and the lowest density value is 0.01